1990
DOI: 10.1002/jcla.1860040610
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal free light chains in urine and their significance in clinical diagnostics: Are they really tumor markers?

Abstract: Bence Jones proteins (monoclonal free light chains of immunoglobulins) are the earliest known biological markers of malignant cell dyscrasia; Bence Jones proteinuria is also present in many types of B cell-related neoplasms. Sometimes, it may also occur in Hodgkin's disease. In some cases, benign monoclonal gammapathy was found to be associated nontumorous diseases as well. The type of monoclonal light chain, the degree of polymerization, and the isoelectric point of the molecule may affect the course of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…13,25 Taken together, these findings suggest that FLC proteinuria in both humans as well as in dogs may not necessarily have deleterious effects on the kidney, and renal damage may depend on intrinsic properties of FLCs that are excreted by the kidney. 17,18,26 Considering our unpublished results of SDS-AGE in dogs displaying an isolated band of 67-72 kDa in urine with negative renal histopathologic findings, we examined dogs with FLC proteinuria to investigate if these animals had an ongoing structural renal disorder or if they represented a different subset of patients with normal renal histopathology and function. The results of the present study demonstrate that FLC proteinuria may be observed in dogs without evident morphologic renal lesions and with normal renal function, as assessed by histologic analysis of percutaneous biopsy specimens examined by light microscopy and by evaluation of the serum concentrations of creatinine, urea, and phosphorus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,25 Taken together, these findings suggest that FLC proteinuria in both humans as well as in dogs may not necessarily have deleterious effects on the kidney, and renal damage may depend on intrinsic properties of FLCs that are excreted by the kidney. 17,18,26 Considering our unpublished results of SDS-AGE in dogs displaying an isolated band of 67-72 kDa in urine with negative renal histopathologic findings, we examined dogs with FLC proteinuria to investigate if these animals had an ongoing structural renal disorder or if they represented a different subset of patients with normal renal histopathology and function. The results of the present study demonstrate that FLC proteinuria may be observed in dogs without evident morphologic renal lesions and with normal renal function, as assessed by histologic analysis of percutaneous biopsy specimens examined by light microscopy and by evaluation of the serum concentrations of creatinine, urea, and phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…8 In humans, the type of FLC excreted (ie, kappa, lambda), differences in the isoelectric point, and degree of polymerization have been correlated with the development of distinct renal disorders, collectively referred to as light-chain nephropathies. 17,18 In contrast to studies in humans, no clear relationship has been established in dogs regarding the identification of urinary FLCs and the presence of morphologic and functional damage to the kidney.…”
mentioning
confidence: 99%
“…Amyloidosis was associated with an increased frequency of the l LC (77% in the A+, 45% in the A±), the presence of LC fragment M r 12 000±18 000 (86% in the A+, 29% in the A±) and a significantly lower (P = < 0.001) isoelectric point of the free LC (pI 4.8 1.1 in the A+, pI 6.2 1.6 in the A±); the latter may contribute to binding to the calcium-P-component characteristic of amyloid deposits [29]. The combination of IEF and immunofixation has been clinically evaluated for detection of BJP in a study of 637 patients with true or suspected lymphoproliferative diseases [115]. The method confirmed microheterogeneity of the free LC and gave a higher rate of detection of BJP than conventional electrophoretic methods with a tenfold increase in sensitivity (0.02 g/L free LC).…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…7,8 MM accounts for about 2% of all cancer mortality. 9 The diagnosis is primarily established by the presence of a monoclonal protein in the serum (malignant plasma cells mainly produce IgG, IgA or Ig light chains), the presence of monoclonal light chains (Bence Jones proteinuria) in urine, 10,11 excess clonal bone marrow plasma cells (>10%), and organ impairment. 6,12,13 The development of novel agents and clinical evidence on combinations have markedly improved the clinical outcomes and overall survival (OS) of MM patients.…”
Section: Introductionmentioning
confidence: 99%